2006
DOI: 10.1007/s00405-005-1018-y
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway surgery: the effect on nasal continuous positive airway pressure titration on obstructive sleep apnea patients

Abstract: The objective of this study was to observe the change in CPAP pressure after nasal and/or tonsil surgery in a retrospective study involving 17 patients unable to tolerate CPAP titration. All patients had two polysomnography studies for titration: one before and another subsequent to upper airway surgical treatment. The results showed a mean age of 49 +/- 9 years, a body mass index of 30 +/- 4 kg/m(2) and an apnea-hypopnea index of 38 +/- 19. Surgical procedures were radiofrequency reduction of the inferior tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 32 publications
1
20
0
4
Order By: Relevance
“…Only 3 studies discussed surgical complications [8,20,24]. Out of these, none observed major complications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 3 studies discussed surgical complications [8,20,24]. Out of these, none observed major complications.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were excluded due to lack of a comparison of pre- and postoperative CPAPs in patients after UAS. Of the 11 studies that met the inclusion criteria, 5 were retrospective [8,16,17,18,19], 4 were prospective [20,21,22,23], and 2 were RCTs [24,25]. UAS performed in the studies included nasal valve repair, radiofrequency ablation to the palate, turbinate reduction, septoplasty, Pillar implants, tonsillectomy, and UPPP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, variable additional factors also impact CPAP compliance, such as individual perception of symptoms and improvement in sleepiness and daily function from initial use of CPAP. For these reasons, larger, well-designed studies are needed to confi rm the durability of any benefi cial effect on CPAP compliance from nasal surgical procedures for individuals with OSA (Zonato et al 2006 ;Weaver and Grunstein 2008 ;Friedman and Wilson 2009 ).…”
Section: Surgical Managementmentioning
confidence: 96%
“…7 Conversely, several studies have demonstrated that multilevel upper airway surgery may improve CPAP compliance and patient symptoms by significantly reducing mean CPAP pressures without observed increases in mask leakage. [8][9][10][11][12] The Pillar implant system is a tissue-sparing, minimally invasive treatment option for patients with snoring and mild levels of sleep apnea. The procedure demonstrates a high level of patient acceptance with low levels of postprocedure discomfort, as evidenced by the 76% of control patients in this study who decided to undergo the procedure a second time to receive the active implants.…”
Section: Discussionmentioning
confidence: 99%